Using cognitive behaviour therapy in counselling non-adherent hypertensive patients: a nurse counsellor perspective - Lee, Khuan (Community Health Society Malaysia, 2016)
Hypertension is a chronic illness that requires the patient to take medicine in the long-term. In hospitals, non-adherent hypertensive patients may be referred to a counsellor by his/her medical officer. Non-adherence is a multifactorial and multifaceted problem that needs intervention through a multidisciplinary health care approach. Counselling non-adherent patients can be a challenging task for a counsellor. This review discusses cognitive behavioural therapy as one of the counselling theories used in counselling hypertensive patients. Some practical applications of cognitive behavioural therapy are suggested to help patients in adhering to antihypertensive therapies.